Prediction Model for Cladding of Ni-Alloys During CMT Welding Process by Using Fuzzy Logic - Iva Deanović; Dejan Marić; Ivan Peko; Sanda Šimunović (Tehnički Vjesnik, 2025)
Maintaining stable conditions during cladding of Ni-alloys is of great importance for achieving a uniform quality of the cladded layer. As cladding of Ni-alloy is performed by the MAG-CMT welding process with a four-component gas on the base material (membrane wall), it cannot be always performed with the same tolerances. Therefore, the MAG-CMT welding process requires constant real-time monitoring and detection of faults in the cladded layer. This paper presents a model based on fuzzy logic. The created model is tested to confirm the proposed prediction model. The prediction accuracy was 93.67%, which proves that the created model can be used for cladding in new automated welding systems. Application of the obtained model shall enable the development of a monitoring system that can identify and classify certain defects occurring during the MAG-CMT welding process.